Obstructive sleep apnea syndrome and sleep quality in hypertensive patients - Bacci,Marcelo Rodrigues (2017)
Summary Introduction: Obstructive sleep apnea and hypopnea syndrome (OSAHS) is one of the developmental factors of high blood pressure (HBP), a relevant global public health problem. OSAHS is characterized by the reduction or complete cessation of respiratory airflow due to intermittent airway collapse. Additionally, significant changes in sleep rhythm and pattern are observed in these patients. Objective: To evaluate the association between OSAHS and sleep quality in essential and resistant hypertensives. Method: A cross-sectional, observational study evaluated 43 hypertensive patients treated at the outpatient clinics of the Faculdade de Medicina do ABC (FMABC) who were medicated with two or more antihypertensive drugs and divided into nonresistant or resistant to treatment. Results: Group I (using up to two antihypertensive agents – 60.47% of the sample) presented mean systolic blood pressure (SBP) of 127.5±6.4 mmHg, mean diastolic blood pressure (DBP) of 79.6±5.2 mmHg, mean body mass index (BMI) of 27.2±5.3 kg/m2 and mean age of 51.2±15.1 years. Group II (using more than two antihypertensive drugs – 37.2% of the sample) presented mean SBP of 132.1±9.3 mmHg, mean DBP of 84.5±5.8 mmHg, mean BMI of 27.2±7.2 kg/m2 and mean age of 55.5±13.4 years. The patients presented low quality of sleep/sleep disorder evaluated by the Pittsburgh Sleep Quality Index (PSQI), which represents a preponderant factor for OSAHS. Conclusion: Patients at high risk for OSAHS had poor sleep quality and high levels of DBP, suggesting a causal relation between these parameters. However, they did not present a higher prevalence of resistant high blood pressure (RHBP).